Effect of urokinase gene knockout on tissue levels of biogenic amines in mice with melanoma - E. M. Frantsiyants; I. V. Kaplieva; E. I. Surikova; I. V. Neskubina; V. A. Bandovkina; L. K. Trepitaki; Y. A. Pogorelova; L. A. Nemashkalova (Сибирский научный медицинский журнал, 2020)
The research aim was to study the dynamics of biogenic amines in the brain, tumor and intact skin of urokinase (uPA) gene knockout mice on day 21 of the B16/F10 melanoma growth.Material and methods. The study included male and female uPA gene knockout (-uPA, n = 38) and wild type mice (+uPA, n = 61). Melanoma was transplanted subcutaneously. Levels of biogenic amines were studied by ELISA in tissues obtained on day 21 of carcinogenesis.Results and discussion. Intact (-uPA) mice showed an increased total content of biogenic amines: in the skin - due to noradrenaline increase by 4.8 times in males and by 4.9 times in females, histamine - by 3.6 times in males and by 1.6 times (p < 0.05) in females, serotonin - by 3.4 times in males and by 8.3 times in females; in the brain - due to noradrenaline increase by 3.5 times in males and by 3.2 times in females, dopamine by 2.1 times in males and by 2.9 times in females, while histamine content decreased. Melanoma development in (-uPA) mice was characterized by: lower levels of adrenaline with high NA concentrations and an increase in the serotonin metabolism in the brain; higher histamine concentrations in the tumor and higher serotonin levels in the skin; similar to (+uPA) mice levels of adrenaline (males) and noradrenaline in the tumor and higher levels of adrenaline in the tumor and histamine in the skin in (-uPA) females.Conclusions. The uPA gene knockout limits the development of stress at the central regulatory level due to lower levels of A together with increasing serotoninergic mediation in the brain, as well as modulates the immune antitumor response due to higher levels of histamine in the tumor and 5 serotonin in the skin, as a result of lower monoamine oxidase activity, in mice with B16/F10 melanoma.